Adaptive teleoperation using intelligent dynamic voting. Issue 10 (2015) - Srinivasan, Lakshminarasimhan; Scharnagl, Julian; Herrmann, Christian; Schilling, Klaus
Abstract: This paper addresses the design of an adative teleoperation framework for spatially displaced robotics. Although teleoperation controllers have been optimized and frameworks developed for single user single robot teleoperation, the same cannot be said for multi-user control of a single remote agent. Typical collaborative teleoperation consists of a group of people working on a single remote robotic system with a user voting interface to decide on the commands sent to the robot. These are majority based systems and just like in a democracy, problems occur. This research is focussed on a system that uses an intelligent and adaptive dynamic voting paradigm in order to enable adaptive teleoperation.